2012
DOI: 10.1039/c2ay05686k
|View full text |Cite
|
Sign up to set email alerts
|

Rapid morphological characterization of isolated mitochondria using Brownian motion

Abstract: Mitochondrial morphology has been associated with numerous pathologies including cancer, diabetes, obesity and heart disease. However, the connection is poorly understood—in part due to the difficulty of characterizing the morphology. This impedes the use of morphology as a tool for disease detection/monitoring. Here, we use the Brownian motion of isolated mitochondria to characterize their size and shape in a high throughput fashion. By using treadmill exercise training, mitochondria from heart and gastrocnem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Prior work in this area often attributed mitochondrial movement to small-scale Brownian motion or limited directed motion. 23 In our previous work we demonstrated that mitochondrial motility follows a continuous distribution in a lognormal fashion in select cell lines. 17 We also demonstrate this type of motion in human blood cells, namely PBMCs consisting of a mixed population of monocytes and lymphocytes.…”
Section: Discussionmentioning
confidence: 93%
“…Prior work in this area often attributed mitochondrial movement to small-scale Brownian motion or limited directed motion. 23 In our previous work we demonstrated that mitochondrial motility follows a continuous distribution in a lognormal fashion in select cell lines. 17 We also demonstrate this type of motion in human blood cells, namely PBMCs consisting of a mixed population of monocytes and lymphocytes.…”
Section: Discussionmentioning
confidence: 93%
“…The RI of an organelle depends on the chemical compositions of the organelle. Since each mitochondrion independently undergoes changes including shrinkage and elongation [12][13][14][15][16], changes in individual mitochondrial RI may also occur, resulting in heterogeneity of mitochondrial RIs. Mitochondrial membrane potential (MMP) in a cell has also been reported to be heterogeneous [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular viscosity is a significant microenvironment parameter, which plays a crucial role in maintaining the normal physiological functions of cells, such as signal transduction, interaction between biomolecules, nutrient transportation and metabolite diffusion at the cellular and subcellular levels. [1][2][3][4] Abnormal intracellular viscosity is associated with malignant changes in physiological processes, especially with the emergence of many diseases, such as diabetes, cardiovascular diseases and even cancers. [5][6][7] For example, the lysosome viscosity of cancer cells is usually higher than that in normal ones and can be used as a marker for tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%